PHYSIOLOGICAL QUALITY AND CHEMICAL COMPOSITION OF Brachiaria brizantha SEEDS AS A FUNCTION OF PRIMING - Cardoso, Eliana Duarte; De Sa, Marco Eustaquio; Haga, Kuniko Iwamoto; Binotti, Flavio Ferreira Da Silva; Costa, Edilson (Univ Estadual Mato Grosso Sul, 2015)
The seed priming has resulted in beneficial effects; however, there is need of specific studies for each species or cultivar. The objective of the present study was to evaluate the effects of priming with different solutions on the physiology quality and chemical composition of Brachiaria brizantha cv. MG-5 seeds. The experimental was arranged in a completely randomized design (CRD), with four replications. The study consisted of mixed solution (1: 1) formed by polyethylene glycol ( PEG 8,000) with a osmotic potential of - 1.5 MPa at 25 degrees C, associated the solutions with nutrients (KNO3 0.2%, Ca(NO3)(2) 0.2%), with plant growth regulators or biostimulant (Cytokinin - CIN 1.62 mg L-1, Gibberellin - GA(3) 0.5 mg L-1, Auxin - IBA 0.5 mg L-1 and Stimulate (R) 1%), and with nutrients plus growth regulators or biostimulant (KNO3 0.2% + GA(3) 0.5 mg L-1, KNO3 0.2% + stimulate (R) 1% and Ca(NO3)(2) 0.2% + GA(3) 0.5 mg L-1) and control treatment. The germination, vigor and chemical composition of the seeds were evaluated. The results suggest that priming had no beneficial effect on physiological quality of seeds; however, the conditioning with PEG 8,000 + KNO3, PEG 8,000 + Ca(NO3)(2) and PEG 8,000 + Biostimulant resulted in increased potassium, calcium and magnesium, respectively, at the chemical composition of B. brizantha cv. MG-5 seeds.
Keywords: Cv. MG-5 Vitoria; plant growth regulator; polyethylene glycol; KNO3; priming